2022
DOI: 10.3389/fpubh.2022.750722
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Model to Predict the Contract Service of Family Doctor: A National Survey in China

Abstract: BackgroundPrevious studies have reported a relatively low utilization of family doctor contract services (FDCS) in China, while the associated factors are unknown. The current study aimed to explore the factors associated with the utilization of FDCS, and then developed and validated a predictive model based on these identified factors.MethodsWe conducted a nationwide cross-sectional study using an online questionnaire, from March 2019 to April of 2019. Routinely collected variables in daily practice by family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…FDCS is a core part of the primary healthcare system opening to the general public. The signing rate of FDCS in the current study was 54.3%, which was similar to the findings in Guangdong (54.7%) and Zhejiang province (50.43%) [ 14 , 15 ], but much higher than that from a nationwide survey in mainland China (approximately 6.0% in the female population) [ 16 ]. Researchers also found lower signing rates among people over 60 years old (28.2%) and with chronic diseases (29.3%) in rural China [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…FDCS is a core part of the primary healthcare system opening to the general public. The signing rate of FDCS in the current study was 54.3%, which was similar to the findings in Guangdong (54.7%) and Zhejiang province (50.43%) [ 14 , 15 ], but much higher than that from a nationwide survey in mainland China (approximately 6.0% in the female population) [ 16 ]. Researchers also found lower signing rates among people over 60 years old (28.2%) and with chronic diseases (29.3%) in rural China [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…The team offers a variety of primary health care services to local residents who contract with the FDCS, such as chronic disease management, physical examinations, referrals, health consultations, and so on. [ 17 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many foreign studies also showed that in less developed countries and regions such as sub-Saharan Africa, tribal culture similar to the family branch system was also critical in environmental protection and HIV prevention and control [ 15 , 16 ]. Meanwhile, Contracted Family Doctor Services [ 17 , 18 ] is conducted throughout the state in accordance with the unified requirements of the National Health Commission in Liangshan Prefecture. An important part of this work is to build an interactive platform for family doctors and contracted residents, providing services such as appointments, consultation, health management, and follow-up visits for NCDs.…”
Section: Introductionmentioning
confidence: 99%